2017
DOI: 10.1002/eji.201646551
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 promotes timely resolution of inflammation in murine gout

Abstract: Gout is a self-limited inflammatory disease caused by deposition of monosodium urate (MSU) crystals in the joints. Resolution of inflammation is an active process leading to restoration of tissue homeostasis. Here, we studied the role of Annexin A1 (AnxA1), a glucocorticoid-regulated protein that has anti-inflammatory and proresolving actions, in resolution of acute gouty inflammation. Injection of MSU crystals in the knee joint of mice induced inflammation that was associated with expression of AnxA1 during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 63 publications
(84 reference statements)
4
49
0
Order By: Relevance
“…Additionally, the endogenous regulator Annexin A1 blocks neutrophil infiltration and promotes monocyte recruitment to the inflamed site, thus contributing to resolution of inflammation. Consistently, deficiency in Annexin A1 has been associated with sustained inflammatory responses [7,[78][79][80].…”
Section: Integrin Regulation By Inflammation-associated Lipid Mediatorsmentioning
confidence: 79%
“…Additionally, the endogenous regulator Annexin A1 blocks neutrophil infiltration and promotes monocyte recruitment to the inflamed site, thus contributing to resolution of inflammation. Consistently, deficiency in Annexin A1 has been associated with sustained inflammatory responses [7,[78][79][80].…”
Section: Integrin Regulation By Inflammation-associated Lipid Mediatorsmentioning
confidence: 79%
“…Akin to our findings, AnxA1 peptide can ameliorate pleurisy, gout, and lung fibrosis. 14,42,55 Of note, Ac2-26 could partially restore host defenses in AnxA1 KO mice, indicating that AnxA1 is important at the time of infection, where it controls inflammation, by reducing neutrophil recruitment and cytokine production, while enhancing bacterial clearance. Importantly, we have confirmed that the AnxA1induced effects relied on FPR2, since in Fpr2/3 KO animals the peptide Ac2-26 did not impact on the number of recruited leukocytes or bacterial burden.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these chemokines, pneumococcal pneumonia in AnxA1 KO mice also resulted in exacerbated levels of TNF-α, reminiscent of what reported in endotoxic shock 44 and gout models. 42 Indeed, AnxA1 can inhibit NF-kB activation, leading to decreased pro-inflammatory cytokines production. 45 Once cells lose this checkpoint, the production of pro-inflammatory cytokines becomes uncontrolled.…”
Section: Discussionmentioning
confidence: 99%
“…Despite our findings, recent analyses show that bone-marrow-derived AnxA1 -/macrophages produced significantly lower secretion of IL-1β when activated with monosodium urate (MSU) crystals and ATP, but not NLRC4 or AIM2 activators (Legionella pneumophila or poly(dA:dT)) [28]. Notably, during the setting of MSU crystal-induced inflammation, the peak of the neutrophil influx was greater, and the resolution was slower in AnxA1 -/mice than in WT animals [29]. These findings are consistent with many studies that have shown an exacerbated inflammatory response in AnxA1 -/mice characterized by a marked leukocyte influx and production of proinflammatory mediators, such as IL-1β and IL-6 [4,6,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with many studies that have shown an exacerbated inflammatory response in AnxA1 -/mice characterized by a marked leukocyte influx and production of proinflammatory mediators, such as IL-1β and IL-6 [4,6,[30][31][32]. Additionally, the administration of the AnxA1 peptide (Ac2-26) 1 h before and 12 h after challenge with MSU crystals induced decreased levels of IL-1β in periarticular tissue, showing the important anti-inflammatory and proresolving activity of this protein on the course of MSU crystal-induced inflammation in mice [29]. Thus, the opposite effects described for the role of AnxA1 on NLRP3 inflammasome-derived IL-1β secretion could be a result of testing different macrophage populations, bone-marrow versus peritoneal-derived, and different strains, BALB/c versus C57BL/6, an important factor in the mouse immunology response [33,34].…”
Section: Discussionmentioning
confidence: 99%